Analisis Pelaporan Kinerja Lingkungan Pada Rumah Sakit Lavalette Tahun 2022 - Erinda Salma Imani; Ida Bagus Ketut Bayangkara (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Lavalette Hospital Malang, located at Jl. WR. Supratman No.10 Malang City, can generate medical and hazardous waste, which can impact the environment. Many healthcare facilities still do not report their environmental performance with GRI standards as it is voluntary. However, to fulfill their environmental and social responsibilities, both external and internal, this environmental performance reporting is helpful. This research uses a qualitative method with a case study at Lavalette Hospital Malang to determine the management of responsibility and disclosure of environmental performance in accordance with GRI Standard 300 guidelines. The data used comes from documentation and interviews with environmental health staff and the Manager of Accounting, Finance, and IT at Lavalette Hospital. Then triangulation analysis was carried out. The results of the analysis show that Lavalette Hospital's environmental performance can be categorized into partial disclosure on GRI index 302: Energy, GRI 303: Water and Effluent, GRI 305: Emissions, GRI 306: Waste, GRI 307: Compliance, and GRI 308: Supplier environmental assessment.